2009
DOI: 10.1155/2009/398264
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antimicrobial‐Resistant Pathogens in Canadian Hospitals: Results of the Canadian Ward Surveillance Study (CANWARD 2007)

Abstract: BACKGROUND: Canadian hospitals as well as hospitals worldwide are increasingly faced with antibiotic-resistant pathogens, including multidrug-resistant (MDR) strains. OBJECTIVES: To assess the prevalence of pathogens, including the resistance genotypes of methicillin-resistantStaphylococcus aureus(MRSA), vancomycin-resistant enterococci (VRE) and extendedspectrum beta-lactamase (ESBL)-producingEscherichia coliin Canadian hospitals, as well as their antimicrobial resistance patterns. MEtHODS: Bacterial isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 25 publications
1
51
4
1
Order By: Relevance
“…In Canada resistance rates are persistently low (Karlowsky et al, 1999;Zhanel et al, 2000;Nichol et al, 2006;Zhanel et al, 2008a;Zhanel et al, 2010b). Results of a recent CANWARD study performed in 2008 among 10 participating Canadian hospitals revealed 3.1% VRE among 320 clinical enterococcal isolates (Zhanel et al, 2010b).…”
Section: Northern Americamentioning
confidence: 99%
“…In Canada resistance rates are persistently low (Karlowsky et al, 1999;Zhanel et al, 2000;Nichol et al, 2006;Zhanel et al, 2008a;Zhanel et al, 2010b). Results of a recent CANWARD study performed in 2008 among 10 participating Canadian hospitals revealed 3.1% VRE among 320 clinical enterococcal isolates (Zhanel et al, 2010b).…”
Section: Northern Americamentioning
confidence: 99%
“…C1-1957 and F1-2057. ) Clinical isolates were collected as part of CANWARD, an ongoing national surveillance system designed to assess pathogen prevalence and antibiotic resistance from respiratory, skin and soft tissue, urinary, and bacteremic infections in Canadian hospitals (18). Twelve sentinel hospitals from across Canada submitted clinical isolates from blood, respiratory, urine, and wound/intravenous site specimens from patients affiliated with hospital clinics, emergency rooms, medical/surgical wards, and intensive care units.…”
mentioning
confidence: 99%
“…In 2007, 7,881 clinical isolates were collected as part of CANWARD (18). The in vitro activity of nemonoxacin was tested against 2,440 gram-positive cocci and gram-negative bacilli.…”
mentioning
confidence: 99%
“…Submitting sites and collection strategy are described elsewhere in the present supplement (2). Isolates had to be deemed clinically significant by the referring laboratory's current specimen work-up protocol.…”
Section: Methodsmentioning
confidence: 99%